Carbonation of loaded RC elements made of different concrete types: Accelerated testing and future predictions. (20th May 2020) - Wang, Xiao-Hui; Val, Dimitri V.; Zheng, Li; Jones, M. Roderick
Highlights: 240-day carbonation results of unloaded and loaded PC, FA and GGBS specimens. Evaluating the carbonation coefficients in test specimens. Estimating the carbonation depths in RC structures after 50 and 100 years exposure. Eurocode durability requirements may be inadequate for 'green' concrete elements. Abstract: Carbonation of concrete can lead to corrosion of reinforcing bars. By this reason its prediction is very important, in particular for durability design, e.g. determining the minimum thickness of the concrete cover. Although carbonation of concrete in reinforced concrete (RC) structures is influenced by applied loading, limited research has been carried out in this area, especially for 'green/low carbon' concretes, i.e. mixes containing supplementary cementitious materials such as fly ash (FA) and ground granulated blast-furnace slag (GGBS). This paper reports the influence of structural loading on carbonation of three types of concrete: Portland cement (PC), PC with 30% of FA and PC with 50% of GGBS, with two water/binder (w/b) ratios (0.40 and 0.55). Test specimens made with these concretes, i.e. 100-mm cubes (unloaded) and RC beams (loaded), were subject to accelerated carbonation (CO2 content of 4%) for a duration of up to 240 days. Results of the tests are presented in this paper along with their analysis, in particular, the evaluation of the carbonation coefficients. The results clearly show a significant influence of loading on carbonation rate. Based on the test results, the estimated effects of loading on carbonation after 50 and 100 years exposure have been calculated. These estimates indicate that the current durability requirements in the Eurocodes may not be adequate for preventing the initiation of carbonation-induced corrosion in tensile zones of RC elements during their design working life.